(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the efforts of the Tian-Shan Kyrgyz in the mid-18th century to establish a unified authority, exemplified by the activities of Ajibiy, leader of the Adygine tribal confederation. Based on Chinese and Manchu historical works from the Qing dynasty and archival documents, the analysis covers the period of the Adygine confederation’s formation, Ajibiy’s endeavors to unite the Kyrgyz tribes under a centralized authority, and the reasons for the failure of this objective. The study conducts a historical analysis based on relevant archival documents preserved in China’s First Historical Archives and other Chinese- language historical works from the Qing dynasty, aiming to fulfill the research objectives. The establishment of the Adygine tribal confederation was driven by the political necessity of the time, as fragmented Kyrgyz tribes—traditionally autonomous and resistant to subordination—faced growing threats and challenges from external powers, necessitating a unified authority to resist these pressures. Despite this need, Ajibiy’s attempt to consolidate all Kyrgyz tribes under a single, centralized authority ultimately failed because the unification conflicted with the interests of powerful neighboring powers.